#### Answer

(3x-8)(2x+7)

#### Work Step by Step

6x$^2$-16x+21x-56
=6x$^2$+21x-16x-56
=3x(2x+7)-8(2x+7)
=(3x-8)(2x+7)

Published by
Brooks Cole

ISBN 10:
0-53449-636-9

ISBN 13:
978-0-53449-636-4

(3x-8)(2x+7)

6x$^2$-16x+21x-56
=6x$^2$+21x-16x-56
=3x(2x+7)-8(2x+7)
=(3x-8)(2x+7)

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.